Evaluation of thyroid lesions by fine-needle aspiration cytology based on Bethesda system for reporting thyroid cytopathology classification among the population of South Bihar - Bhartiya, Richa; Mallik, Mahasweta; Kumari, Nawanita; Prasad, Brijendra Narayan (Indian Journal of Medical and Paediatric Oncology, 2016)
Background: Fine-needle aspiration (FNA) of the thyroid gland has proven to be an important and widely accepted, cost-effective, simple, safe, and accurate method triaging patients with thyroid nodules. Awareness and understanding of wide spectrum thyroid disorders are of great value because most lesions are treatable by medical or surgical management. Aim: The aim of this study is to determine the accuracy of FNA cytology (FNAC) in the diagnosis of thyroid lesion using the Bethesda system for reporting thyroid cytopathology nomenclature (BSRTC) and to correlate these with histopathological findings. Materials and Methods: FNA was performed in 238 patients from January 2014 to October 2015 at a Tertiary Teaching Hospital in Bihar presenting with the thyroid swelling and its histopathological correlation was done in 105 patients. Results and Observations: Out of 238 patients with thyroid swelling, majority were females (196) and in younger age group (n = 104 [43.6%], 21–40 years). In 224 cases, adequate smears for cytological interpretation were obtained. Among them, colloid goiter was the most common lesion. Of these, 105 cases were surgically treated, and tissue was submitted for histopathological examination, which showed 97 nonneoplastic lesions and eight neoplastic lesions. Conclusion: FNAC is rapid, simple, safe, and cost-effective diagnostic modality in the investigation of thyroid disease with high sensitivity, specificity, and accuracy. It can be used as an excellent first-line method for investigating the nature of lesion. Bethesda system is very useful as it is simplified, systematic, standardized system for reporting thyroid cytopathology, which provides better communication between cytopathologist and clinicians, leading to more consistent management approach.
Keywords: Bethesda nomenclature; colloid goiter; follicular neoplasm; papillary carcinoma thyroid; thyroiditis